Federal Indian Law as a Structural Determinant of Health. (December 2019) - Hoss, Aila
Federal Indian law is the body of law that defines the rights, responsibilities, and relationships between three sovereigns, Tribes, states, and the federal government. This area of law has defined, oftentimes poorly, the contours of treaty rights, criminal and civil jurisdiction, economic development, among other issues. Much has been documented in terms of the implications of social, legal, political, and economic systems that perpetuate inequities amongst American Indian and Alaska Native populations. There has also been substantial research on health inequalities. Yet, there has been less discussion on the role of law in perpetuating these adverse health outcomes in these populations. The social and structural determinants of health are the factors and conditions, such as housing, education, and politics, that create health disparities. For years, law has been described as a tool to promote health and even a determinant of health. And while research has explored Tribal health laws and federal Indian health policies, more needs to be analyzed in terms of the role of foundational principles of federal Indian law in perpetuating health disparities. This article argues that federal Indian law is a structural determinant of health by linking health disparities to the constructs of this body of law.